2017
DOI: 10.1287/moor.2016.0833
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Ordering Policy for Inventory Systems with Quantity-Dependent Setup Costs

Abstract: We consider a continuous-review inventory system in which the setup cost of each order is a general function of the order quantity and the demand process is modeled as a Brownian motion with a positive drift. Assuming the holding and shortage cost to be a convex function of the inventory level, we obtain the optimal ordering policy that minimizes the long-run average cost by a lower bound approach. To tackle some technical issues in the lower bound approach under the quantity-dependent setup cost assumption, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 53 publications
1
40
3
Order By: Relevance
“…Our results differ from those in [12,15,16,26,27]. These papers deal with the long-term average cost criterion for continuous-time models, and indicate that under the respective circumstances an (s, S) policy is optimal.…”
Section: Introductioncontrasting
confidence: 88%
“…Our results differ from those in [12,15,16,26,27]. These papers deal with the long-term average cost criterion for continuous-time models, and indicate that under the respective circumstances an (s, S) policy is optimal.…”
Section: Introductioncontrasting
confidence: 88%
“…We begin by examining the classical model that has been studied by Bather (1966), Sulem (1986), Dai and Yao (2013), and many others. In particular, we show that Theorem 5.1 extends the result in He et al (2017) and verifies optimality as a result of our analytical approach. We then examine a drifted Brownian motion process with reflection at {0} using a nontraditional cost structure.…”
Section: Drifted Brownian Motion Inventory Modelssupporting
confidence: 78%
“…In contrast, in Helmes et al (2017) we showed optimality in a smaller class of ordering policies for the general models under a more restrictive set of conditions. Optimality of (s, S) policies for the general class of admissible policies for two examples from He et al (2017) and Helmes et al (2017) was established using ad hoc methods specifically tuned to the examples.…”
Section: Introductionmentioning
confidence: 99%
“…We do note however that in a recent study, He et al. () has shown that in a different stochastic setting where demand is governed by a Brownian motion, ( s , S )‐optimality holds when the fixed‐plus‐proportional ordering cost structure is relaxed to allow the setup cost to be a bounded and lower semicontinuous function of the order quantity.…”
Section: Introductionmentioning
confidence: 81%